Analysis of Household Consumer Preferences Based on Horse Meat Attributes in Determining Purchases at Traditional Markets in Jeneponto Regency - Nursamsi; Ahmad Ramadhan Siregar; Abdul Razak Munir (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
Jeneponto Regency is one of the largest horse sales centers in South Sulawesi. Horse has considerable potential as a source of meat for food. Horse meat can be obtained from traders in traditional markets at a price of around IDR 150.000/kg. The preference of horse meat consumers is a person's choice of likes or dislikes towards the choice of horse meat products consumed. Consumers pay attention on various kinds of attributes attached to horse meat that are used as considerations in making purchasing decision. This study aimed to analyze consumer preferences for horse meat and the effect of consumer preferences for horse meat at Traditional Markets in Jeneponto Regency on consumer decisions. This research was carried out at traditional markets in Jeneponto Regency, namely Tolo Market and Karisa Market in December 2021. The method used in this research is a quantitative approach. The focus of this study was to reveal household consumer preferences based on horse meat attributes with a sample of 168 household consumer respondents, consisting of 100 respondents analyzed by using Cochran Q-Test analysis and 68 respondents analyzed by using regression analysis. The results indicated that there were five attributes that were most preferred by consumers, namely X1 (red liver, high fat content, lower part, cheap), X2 (brownish red, low fat content, upper part, standard), X3 (brownish red, high fat content, upper part, cheap), X4 (brownish red, no fat, lower part, standard), and X5 (liver red, no fat, lower part, standard) and the influence of consumer preferences in this case the 5 attributes that have been combined on the purchasing decisions had a significant and positive effect of 73.8%, the value of Sig. F is 0.000 so that it is less than alpha 0.05, and the t-count value of X1 (8.446), X2 (4.865), X3 (5.468), X4 (7.774), X5 (8.741) is greater than the t table value of 1.667. Keywords: Horse meat, consumer preferences, attributes.